Analisis Pengelolaan Ritel PT Angkasa Pura 1 di Bandar Udara Internasional Adi Soemarmo Surakarta - Fetika Ervida Naim (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study: to analyze retail management at Adi Soemarmo International Airport, Surakarta; Describe the benefits of retail, supporting factors and inhibiting factors of retail management. This type of descriptive qualitative research. The results showed: Retail management planning, organizing, directing and supervising. An important benefit of retail at the airport is that passengers make it easier to find products. Supporting factors for managing retail promotions, large number of passengers, attractive physical evidence, and quality workforce. Meanwhile, the inhibiting factors for managing retail where rent is expensive, access to the airport is not as easy as having your own retail store, due to the Covid-19 pandemic, the number of passengers has dropped drastically.